A Five-year Antimicrobial Susceptibility Trend among Bacterial Isolates from Blood Culture at a Tertiary Health Care Facility: A Retrospective Study - Satabdi Sahu; ayanti Prava Behera; Snigdha Rani Panigrahy; Swapna Mahapatra; Abinash Panda; Sandipta Subadarshani; Sanghamitra Padhi (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Antimicrobial Agents (AMA) frequently used to treat Bloodstream Infections (BSI) when inappropriately used give rise to Antimicrobial Drug Resistance (AMR). Monitoring blood culture isolates with Antimicrobial Susceptibility Testing (AST) determines pattern of antibiotic resistance can help to promote its rational use. Aim: To estimate clinicodemographic associates and trend of Antimicrobial Susceptibility among bacterial blood culture isolates over five-years (2019-2024). Materials and Methods: This study was a retrospective recordbased design done in the Department of Pharmacology in collaboration with the Department of Microbiology in Maharaja Krushna Chandra Gajapati, Medical College and Hospital, Berhampur, Odisha, India. All consecutive laboratory confirmed cases reported for blood culture AST using Clinical and Laboratory Standards Institute (CLSI) guidelines from December 2022 to December 2024 over five-year 2019-2024 were analysed for resistance and sensitivity pattern. All consecutive samples were taken and 1572 cases adhering to inclusion criteria were included. Percentage of AMA resistant and sensitive to different clinico-demographic associates was computed using Jamovi version 2.7.14. Results: There was a rising trend of Antimicrobial Resistance (AMR) from 12.5% to 14.5% from 2019-2024. Statistically significant association p